2011
DOI: 10.1001/archinternmed.2010.539
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Hypoglycemia Among Elderly Patients With Poor Glycemic Control

Abstract: Hypoglycemia in elderly patients with diabetes increases the risk of cardiovascular and cerebrovascular events(1), progression of dementia(2), injurious falls(3), emergency department visits, and hospitalization(4). Hypoglycemic episodes are difficult to diagnose in this population and are easily missed by intermittent finger-stick measurements. Recent large studies(5) have shown lack of benefit and sometimes higher risk of morbidity and mortality with tight glycemic control, especially in older adults. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(125 citation statements)
references
References 14 publications
2
117
1
5
Order By: Relevance
“…Hypoglycemia was only slightly higher in those randomized to saxagliptin, although this excess has been shown to have occurred in those on background sulphonylureas and with a baseline HbA 1c ,7.0% (53.0 mmol/mol) (33). This finding is important because age is an independent risk factor for hypoglycemia (10,34,35). Furthermore, age-related comorbidities and severe oscillations in glucose levels in elderly patients due to poor or noncompliant management may increase the risk for hypoglycemia and may contribute to cognitive disorders and physical debilitation (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…Hypoglycemia was only slightly higher in those randomized to saxagliptin, although this excess has been shown to have occurred in those on background sulphonylureas and with a baseline HbA 1c ,7.0% (53.0 mmol/mol) (33). This finding is important because age is an independent risk factor for hypoglycemia (10,34,35). Furthermore, age-related comorbidities and severe oscillations in glucose levels in elderly patients due to poor or noncompliant management may increase the risk for hypoglycemia and may contribute to cognitive disorders and physical debilitation (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…Fear of injections also increases patient reluctance about the initiation of insulin. Consistent with this finding, Munshi et al found that even after the recommendation of the American Geriatric Society for the elevation of targeted HgA1c levels to over 8%, hypoglycemia occurrence in this population is not precisely known and remains an area for further investigation (19).…”
Section: Discussionmentioning
confidence: 70%
“…A case study 117 involving the use of continuous glucose monitoring to measure hypoglycaemia in older adults with diabetes found that simply relaxing HbA 1c goals may not be adequate to protect frail older adults against hypoglycaemia. They found 'an unexpectedly high frequency of hypoglycaemic episodes in older adults with poor glycaemic control'; 117 this was true of those with type 2 diabetes as well as of those with type 1 diabetes. The authors concluded that there is a need for treatment regimens that better match patients' self-care abilities, although they did not explore further what such regimens might look like.…”
Section: Diabmentioning
confidence: 99%
“…The authors concluded that there is a need for treatment regimens that better match patients' self-care abilities, although they did not explore further what such regimens might look like. 117 …”
Section: Diabmentioning
confidence: 99%